Localized calcification of hydrophilic acrylic intraocular lenses after posterior segment procedures. Issue 12 (December 2019) - Balendiran, Vaishnavi; MacLean, Kyle; Mamalis, Nick; Tetz, Manfred; Werner, Liliana
Abstract : Purpose: : To describe the clinical and laboratory findings in a series of cases of hydrophilic acrylic intraocular lens (IOL) opacification after posterior segment procedures. Setting: : John A. Moran Eye Center, University of Utah, Salt Lake City, USA. Design: : Experimental study. Methods: : Thirty hydrophilic acrylic IOLs were explanted after various posterior segment procedures (pars plana vitrectomy, intravitreal antivascular endothelial growth factor injections) because of localized central anterior surface and subsurface optic opacification associated with decreased visual function. Once received by the laboratory in the dry state or in fixative by the explanting surgeons, microscopic, histochemical (alizarin red), and surface analysis (scanning electron microscopy [SEM], energy‐dispersive X‐ray spectroscopy [EDS]) evaluations were performed on the IOLs. The surgeons were sent a questionnaire to obtain information pertinent to each case. Results: : Of the 30 explanted IOLs, 9 hydrophilic acrylic designs from 7 different manufacturers were identified. Gross microscopy and light microscopy showed granular deposits in a dense round pattern of distribution within the margins of the capsulorhexis or pupil on the anterior surface/subsurface of the IOLs. The granules stained positive for calcium with alizarin red. On SEM coupled with EDS, the granular deposits were found to comprise calcium and phosphate. Conclusions: : A localized pattern of anterior surface/subsurface calcification was seen on hydrophilic acrylic IOLs from various manufacturers. The calcification resembled the pattern seen on calcified IOLs after anterior segment procedures using intracameral injections of air or gas. This calcification of hydrophilic acrylic IOLs is likely the result of blood‐aqueous barrier breakdown from repeated intraocular procedures.